Produção da liga quasicristalina do sistema AlCuFe por moagem de alta energia - Viana, Silvana Garcia (2009)
Quasicrystals, whose structures present non-crystallographic symmetry, have attracted considerable interest due to their structural, electronic and magnetic properties. Besides, interaction among these properties has also been investigated. In general, quasicrystals are good electric and thermal insulating materials, they are very hard, resistant to friction and to waste, and some are good hydrogen keeper. In the last years, High Energy Milling (HEM), a technique of powder metallurgy developed during the 60's, was established as a viable method of processing in the solid state to the production of several metastable and stable quasicrystalline phases (QC). In this work, milling conditions and thermal treatment to obtaining Al62,2Cu25,5Fe12,3 icosahedral phase were studied. For this reason, the work was divided in two stages: the first was the formation of a sample referential obtained in induction oven and the second stage was High Energy Milling (HEM) process to obtain the quasicrystalline alloy, using as base, the sample reference to definition of this composition. The alloy formation by HEM process of elementary powders with a combination of thermal treatment was investigated through x-ray difratometry and differential thermal analysis (DTA). The specimens were prepared with a milling time variation of 10 h, 20 h, 30 h and 40 h in a Frittsch Pulverisette 5 planetary ball milling and cooking temperatures of 450°C, 600°C, 720°C and 800°C. The formation of Al62,2Cu25,5Fe12,3 quasicrystalline alloy, by MAE, showed quite satisfactory results compared with other existent alloys in the literature. It can be concluded that it is possible to obtain the formation of the quasicrystalline phase with short time of milling low temperature of thermal treatment for Al62,2Cu25,5Fe12,3 alloy obtained by HEM process.